Design, growth, fabrication and characterization of GaN based blue light emitting diode - Kyaw, Zabu (2016)
The generation of white light using the combination of III-nitride blue light-emitting diodes (LEDs) with accompanying phosphors has attracted great attention from commercial and academic communities. Much of this interest comes from the need to improve the energy efficiency of lighting technology. This thesis research work aims to enhance the efficiency of blue LEDs for lighting and display applications. There are two possible aspects to increase the efficiency of InGaN/GaN based blue LEDs. The first is to improve the eﬃciency of light emission in the active region, i.e., the internal quantum eﬃciency (IQE). The second is to increase the ratio of photons extracted out of the LEDs to those created in the active region, i.e., the light extraction eﬃciency (LEE). Hence, the thesis research work focuses on the improvement of these two critical efficiencies. In this thesis, first, the basic GaN MOCVD growth is introduced, which is a two-step growth process of low-temperature buffer growth followed by high-temperature epilayer growth. The early stage high-temperature (HT) grown GaN is studied, which has an effect on the subsequent undoped-GaN crystal quality and the performance of LEDs. It was found that higher temperature of initial HT grown GaN leads to better LED performance with a substantial increase in IQE. Second, the LED chip fabrication process is established and the LED chip performance achieved is found to be well comparable to the high end results previously reported. Subsequently based on the optimized material growth and chip fabrication processes, novel designs of the device architecture of InGaN/GaN based LEDs are also proposed and systematically studied for the further improvement of the IQE and the LEE. Among the main issues affecting the LED performance are (1) electron overflow from the quantum wells (QWs) to the p-GaN region, which gives rise to the quantum efficiency droop at high current density, and (2) current crowding effect for InGaN/GaN LEDs grown on insulating sapphire substrates with lateral current injection scheme, which causes non uniform light emission across the device area. In the thesis, we proposed a new design comprising of lattice matched NPNPN-GaN junctions in the n-GaN region that serve both as the current spreading layer and the electron blocking layer. Since the growth temperature of the NPNPN-GaN junctions in the n-GaN region is not limited to low temperature range and there is a larger room for optimizing the growth, an excellent crystal quality of the NPNPN-GaN junctions in the n-GaN region is achieved. The NPNPN-GaN junctions in the n-GaN region with these advantages hold great promise for improving the InGaN/GaN LED performance for two reasons: First, the electron overflow is reduced due to the blocking barriers generated in the NPNPN-GaN junctions. Second, the current crowding is reduced due to the fact that the NPNPN-GaN junctions increase the layer resistivity vertically and thus promote the lateral current spreading. Also, the performance of LEDs can be largely limited by electron leakage out of the multiple quantum wells (MQWs) active region and low hole injection efficiency. We proposed and demonstrated an electronic structure comprising of three-step undoped-InGaN with In composition grading from low In content to high In content, i.e., In0.015Ga0.985N/In0.052Ga0.948N/ In0.09Ga0.91N, inserted between the GaN last quantum barrier (LQB) and the p-type electron blocking layer (EBL). The proposed three-step undoped-InGaN LQB simultaneously both reduces electron overflow (by suppressing the electron leakage) and promotes hole injection (by improving the hole transport). The three-step undoped-InGaN LQB architecture epi-design and structure does not add any difficulty to the growth process or cause any degradation of the radiative recombination. We found that the low In content at the interface of GaN LQB will increase effective potential barrier height for electrons (by suppressing the electron leakage) and better hole transport into QWs, while high In content at the interface of p-AlGaN EBL will decrease the effective potential barrier height for holes, promoting hole injection from the hole source p-GaN. Finally, as well known, a significant portion of the light generated in the GaN epi-layers is trapped inside due to the total internal reflection, which leads to the low light extraction efficiency (LEE). The critical angle for the total internal reflection is 23.6 in GaN (for n=2.5 at 440 nm) when interfaced with air (n=1). Thus, the resulting extraction efficiency from the planar GaN surface into the air is only about 4% of the generated light. To improve LEE, we proposed room-temperature larger-scale highly ordered nanorod-patterned ZnO films on InGaN/GaN LEDs. We developed a cost-effective and efficient ZnO nano-imprinting process to directly create the large-scale ordered ZnO nanorods along with a wetting film on top of the LEDs for excellent LEE enhancement. The introduction of the imprinted ZnO nanorods does not degrade electrical properties of the final LEDs thanks to the room-temperature processing. As a result of light scattering effect, combined with the enhancement of light extraction through the ZnO nanorod sidewalls, the LEE of the integrated ZnO-nanorod/GaN LED is remarkably improved. With these investigations, the thesis studied the problems of internal quantum efficiency and light extraction efficiency. The findings of this thesis hold great promise for designing and making enhanced InGaN/GaN LEDs.